Genetic Features of mcr-1 Mediated Colistin Resistance in CMY-2-Producing Escherichia coli From Romanian Poultry - Maciuca, Iuliana E.; Cummins, Max L.; Cozma, Andreea P.; Rimbu, Cristina M.; Guguianu, Eleonora; Panzaru, Carmen; Licker, Monica; Szekely, Edit; Flonta, Mirela; Djordjevic, Steven P.; Timofte, Dorina (Frontiers in Microbiology, 2019)
Colistin is a last resort antibiotic used for the treatment of human infections associated with carbapenemase-producing Enterobacteriales. Here, we evaluated the occurrence of mcr-1 and -2 plasmid-mediated colistin resistance in colistin and/or carbapenem resistant human clinical Enterobacteriales and other gram-negative bacteria (n = 543) as well as third generation cephalosporin-resistant (3GCR) Escherichia coli isolates from poultry abattoir workers (n = 15) and poultry fecal samples (n = 92) collected from two geographically separate abattoirs in Romania. which revealed that mcr-1 was present within four sequence types (STs): ST744 (n = 7), ST57 (n = 7), ST156 (n = 2), and ST10 (n = 1). Within STs, serotypes were conserved and, notably, all except one of the mcr-1-positive isolates were found to exhibit fluoroquinolone-resistance (FQR) associated SNPs in both gyrA and parC. While there were variations in genotypes, all isolates belonging to ST744, ST57, and ST156 were rich in resistance determinants, carrying aminoglycoside-modifying enzymes genes, sulfonamide resistance gene blaTEM–1 as well as blaCMY–2 AmpC β-lactamase resistance genes. They also exhibited high similarity in carriage of virulence genes; ST10, however, only carried the mcr-1 gene. Whole genome sequencing (WGS) analysis also revealed that although the mcr-1 gene was identified in a diverse population of E. coli, two STs (ST57 and ST744) predominated and interestingly, were found in isolates across both abattoirs providing evidence for clonal transmission. Also, two main genomic contexts of mcr-1 isolates were revealed with all ST57 isolates harboring the mcr-1 gene between two copies of ISApl1 (or the Tn6330 transposon) whilst a common mcr-1 containing scaffold, highly similar to IncX type mcr-1-bearing plasmids (pWI2-mcr, Accession number: LT838201), was present among mcr-1 isolates of varying phylogenetic backgrounds (ST10, ST744 and ST156). The high prevalence of the mcr-1 gene in poultry E. coli isolates with co-resistance to cephalosporins and quinolones, in a country where antimicrobial use in food production species is poorly regulated, is concerning and the findings from this study should lead to better surveillance of antimicrobial resistance (AMR) in food-production animals in Romania.